DIVIDENDS PAYOUT, MARKET CAPITALIZATION AND MARKET VALUE OF MANUFACTURING FIRMS IN NIGERIA (American Journal of Business Management, Economics and Banking, 2025)
The aim of the study was to determine the nature of relationship between dividend payout, market capitalization, inflation and market value of manufacturing firms in Nigeria using secondary data obtained from firms listed on Nigeria stock exchange between 2013 and 2021. Multiple regression analysis to ascertain nature of relationship was used and Hausmann Test for selection of model. Also, various diagnostic tests were conducted on data set. The study found a positive significant relationship of dividend and inflation on market value measured by Tobin Q and Price earnings ratio. Based on findings we conclude dividend and inflation impact firm value positively. We noted market capitalization positively and insignificantly affect Tobin Q and positively and significantly affect Price earnings ratio. We conclude market capitalization has a positive effect on market value. We noted negative significant relationship of dividend and inflation on Enterprise value and a negative insignificant relationship of market capitalization on Enterprise value. We conclude a trade-off exist between the variables. Increases in variables increase market value while at the same time dampening enterprise value. Based on findings, we conclude that our study negates Dividend irrelevance theory and aligns with signaling theory and bird in hand theory which suggests that dividends impact firm value. We recommend that to maximize firm value corporate Managers should design an efficient and effective dividend policy depending on the firms financing and investment need taking into consideration the interest of shareholders.